The teacher's survival guide - Thody, Angela; Gray, Barbara; Bowden, Derek (London : Continuum, 2000)
This book is divided into five parts: Beginnings; Success with pupils; Success with colleagues; Success with yourself; and Endings.
Keywords: Education; Teachers; Teachers -- Job satisfaction; Teachers -- Job stress; Teacher morale